Dynamic Modeling of 3-Dimensional Marine Fields: Unleashing the Power of Convolutional Transformers for Advanced Environmental Analysis - Rodrigues, Inês Ferreira (2024)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence